SYSTEM FOR VEHICLE ROUTING PROBLEM ALGORITHMS ANALYSIS - Sztajerowski, Wiktor; Ochelska-Mierzejewska, Joanna; Kucharski, Jacek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Paper concerns the software system supporting the analysis of different cases of solving VRP by various algorithms. VRP has been characterised and application structure has been presented. Illustrative experimental results show the usefulness of the system.